2017
DOI: 10.1017/s1041610216002428
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and adaptive functioning in older people attending drug and alcohol services

Abstract: The results suggest that cognitive impairment in this group is common. The assessment of cognitive status for this older group of patients should not only include the identification of cognitive impairment but also encompass mental health and social functioning. A greater understanding of the needs of this cohort will also enable better co-ordination with other health and welfare services tailored to this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…While some studies show alcohol use to be protective of brain functions over the life course, other studies show cognitive impairment and various dementias are associated with alcohol and other substance use, whether active or past use [36]. An Australian study of OA attending outpatient treatment for SUD discovered that 66% met criteria for mild or severe cognitive impairment [37]. While symptoms of some cognitive impairments subside once an OA achieves abstinence, others may worsen regardless.…”
Section: Kuerbismentioning
confidence: 99%
“…While some studies show alcohol use to be protective of brain functions over the life course, other studies show cognitive impairment and various dementias are associated with alcohol and other substance use, whether active or past use [36]. An Australian study of OA attending outpatient treatment for SUD discovered that 66% met criteria for mild or severe cognitive impairment [37]. While symptoms of some cognitive impairments subside once an OA achieves abstinence, others may worsen regardless.…”
Section: Kuerbismentioning
confidence: 99%
“…22,23 To our knowledge, this is the first report to show these relationships in older adult inpatients with SMI. The current lack of information on this potentially important topic, combined with demographic trends in the US population, 6,7 should occasion a call for more intensive research in this domain. While we did observe differences in outcomes across race, these findings were not systematic across LOS and MEDCO.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of alcohol use disorder, the influence of SUD on the course of mental illness in older‐age adults has received little attention in gerontology and psychiatry, particularly in those with SMI requiring hospitalization. The anticipated increase in older‐adults in the general population mandates enhanced focus on research and treatment in older‐age adults with mental illness and SUD . Notably, in the next 5 years, the number of older adults in the United States requiring treatment for SUD will increase to 4.4 million compared with 1.7 million in 2000 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Monds et al. (2017) found that nearly two‐thirds of adults aged 50 and over attending a drug and alcohol treatment service showed signs of CI.…”
Section: Introductionmentioning
confidence: 89%